Meta-Analysis of Yield-Related and N-Responsive Genes Reveals Chromosomal Hotspots, Key Processes and Candidate Genes for Nitrogen-Use Efficiency in Rice - Kumari, Supriya; Sharma, Narendra; Raghuram, Nandula (Frontiers in Plant Science, 2021)
Nitrogen use efficiency (NUE) is a function of N-response and yield, controlled by many genes and phenotypic parameters that are poorly characterized. This study compiled all known yield-related genes in rice and mined them from N-responsive microarray data to find 1,064 NUE-related genes. Many of them are novel genes hitherto unreported as related to NUE, including 80 transporters, 236 transcription factors, 41 MicroRNAs, 91 kinases and 8 phosphatases. They were further shortlisted to 62 NUE candidate genes following hierarchical methods, including QTL co-localization, functional evaluation in literature and protein–protein interactions. They were localized to chromosomes 1, 3, 5 and 9, of which chromosome 1with 26 genes emerged as a hotspot for NUE spanning 81 % of the chromosome. Further, co-localization of NUE genes on NUE-QTLs resolved differences in earlier studies that relied mainly on N-responsive genes regardless of their role in yield. Functional annotations and protein-protein interactions for all the 1,064 NUE-related genes as well as the shortlisted 62 candidates revealed transcription, redox, phosphorylation, transport, development, metabolism, photosynthesis, water deprivation, hormones and stomatal function among the prominent processes. In silico expression analysis confirmed differential expression of the 62 NUE candidate genes in a tissue/stage-specific manner. Experimental validation in two contrasting genotypes revealed that high NUE rice shows better photosynthetic performance, transpiration efficiency and internal water use efficiency, than the low NUE rice. Feature Selection Analysis independently identified one-third common genes at every stage of hierarchical shortlisting, offering priority targets to validate for improvingcrop NUE.